Visualización óptima de campos escalares y vectoriales utilizando GPUs - Martínez Melchor, Apolinar (Universidad Autónoma Metropolitana, 2015)
El presente trabajo continúa con la línea de investigación del proyecto 155070 de CONACYT cuyo título es “Uso de tarjetas gráficas para el análisis de la función de onda”. En el Área de Fisicoquímica Teórica se realizan estudios sobre la estructura electrónica, las propiedades físicas y químicas, la relación estructura-actividad y la reactividad de las especies químicas. En consecuencia, este trabajo de investigación se centró en la Visualización Optima de Campos Escalares y Vectoriales utilizando GPUs; con el fin de proveer de una herramienta de software. molS, es la herramienta software desarrollada, que permite realizar las tareas de calcular sistemas de moléculas sobre tarjetas gráficas y visualizar en tiempo real campos escalares.; The work presented in this document is entitled “Implementation/Use of graphics cards in weave function analysis”. This research work is comprised within the research lines of Project 155070, a wider project registered under National Council for the Sciences and Technology (CONACYT, for its acronym in Spanish). This research work revolved around the issues of developing and implementing Optimal Visualization of Scalar and Vector Fields through GPUs. The goal was to provide the Physicochemistry Department of The Autonomous Metropolitan University Campus Iztapalapa (UAM - I, for its acronym in Spanish) with a software tool for the analysis of molecular chemical bonds. The aforementioned software tool has been developed and named “molS”. This tool allows the user to operate graphics cards to calculate the geometry of molecular systems and to obtain real- time visualization of the molecular systems. This document contains a description for the theoretical framework, the design and the development of “molS”. Also, this document presents the process trough which “molS” was refined into an efficient software tool. Thus, this work contains the exploration on different possible schemes of graphics card’s memory usage during the development and implementation of “molS”. Finally, this document presents different example cases of ussage and aplication of “molS”.